The spatial, temporal and volumetric analysis of a large mud volcano province within the Eastern Mediterranean. (March 2017) - Kirkham, Christopher; Cartwright, Joe; Hermanrud, Christian; Jebsen, Christopher
Abstract: This paper documents and describes through the use of 3D seismic data a prolific mud volcano province within the Eastern Mediterranean. As many as 386 mud volcanoes were mapped within the post-salt succession of the western slope of the Nile Cone, offshore Egypt, using high resolution 3D seismic data. The mud volcanoes within this field display significant geometrical variability in diameter (c. 550 m to c. 5660 m), height (c. 25 m to c. 510 m) and volume (c. 0.1 km 3 to c. 3.3 km 3 ) and lie at depths ranging from c. > 6000 m subsea to c. 3100 m at the seafloor. A close spatial relationship between mud volcanoes and base-salt depressions and regions of anomalous thinning within the immediate pre-salt succession, combined with documented core samples taken from mud volcanoes within this region present a powerful argument for a pre-salt source of mud. 3D seismic interpretation and volumetric analysis of these mud volcanoes and their source region permit the definition and quantification of their depletion zones. A conceptual model for a dynamic liquefaction and sediment withdrawal process is proposed whereby mud is fed into a central conduit as the depletion zone propagates radially and episodically outwards resulting in a the formation of a concentric depletion zones. Prolonged mud volcanism within this region over the last ∼5.3 Ma implies the potential for long lived pre-salt overpressure and continued mud volcanism following the catastrophic hydrodynamic impact of the Messinian Salinity Crisis. It is suggested that the scale of mud volcanism means that this region should be considered as among the largest mud volcano provinces in the world. Highlights: A large mud volcano province the extent of which was previously unrecognised. Long lasting pre-salt overpressure and mud volcanism since the Messinian. Seal breaching of a thick unit of Messinian evaporites by remobilised mud. The first quantitative volumetric analysis of the depletion zones of mud volcanoes. Conceptual model for a dynamic liquefaction and mud withdrawal process.